THE ROLE OF RISK MANAGEMENT IN IMPROVING THE QUALITY OF EDUCATION IN ACADEMIC INSTITUTIONS - Tomi Bidjai; Anik Mufarrihah (Indonesian Journal of Education (INJOE), 2025)
This research aims to examine the role of risk management in improving the quality of education in academic institutions through a literature review approach. The complexity of the challenges faced by educational institutions, ranging from operational uncertainty to policy changes and global dynamics, demands the implementation of effective and structured risk management strategies. This study collects and analyzes scientific literature from various leading sources, such as Scopus, Google Scholar, and ProQuest, spanning the years 2015–2025. The analysis was carried out thematically to identify implementation trends, supporting and inhibiting factors, as well as strategic implications of risk management on the quality of education. The results of the study show that risk management contributes significantly to achieving educational quality through improving governance, data-based decision making, and strengthening an adaptive organizational culture. Implementing strategies such as risk identification, mitigation, risk communication and regular evaluation has been proven to increase institutional resilience to crises and dynamics of change. This study recommends integrating risk management into education policies and strengthening institutional capacity as important steps towards a quality, sustainable and competitive education system